Complexity and diversity in c-type cytochrome biogenesis systems. (1st February 2005) - Allen, J.W.A.; Ginger, M.L.; Ferguson, S.J.
Abstract : c -type cytochromes contain haem covalently attached to protein by thioether bonds formed post-translationally and requiring a dedicated biogenesis apparatus. Three biogenesis systems, found in different cell types, are well known. Here we discuss emerging evidence for at least one additional system, for unanticipated diversity in the location of the systems and for the co-existence of multiple systems in some cells.